2016
DOI: 10.1016/s0167-8140(16)32829-8
|View full text |Cite
|
Sign up to set email alerts
|

EP-1579: Room scatter effects in Total Skin Electron Therapy: a Monte Carlo study

Abstract: Telephone: (972) 4 7772015; Fax: (972) 4 7773154. AbstractPurpose: Total Skin Electron Irradiation (TSEI) is a complex technique which usually involves the use of large electron fields and the dual-field approach. In this situation, many electrons scattered from the treatment room floor are produced. However, no investigations of the effect of scattered electrons in TSEI treatments have been reported. The purpose of this work was to study the contribution of floor scattered electrons to skin dose during TSEI t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The Monte Carlo simulation work of Nevelsky et al reported peak floor scatter contributions at 20 cm above the floor to be +3%, −3%, and −5% for iron, PVC, and water, compared to concrete, given a SSD = 400 cm and gantry angle 17° above the horizontal. These magnitudes are larger than those measured with the Cherenkov imaging method (+2.4%, 0.0%, −1.6%), even with a 13° increase in gantry angle (30° vs 17° above the horizontal, more directly impinging the floor) at the shorter SSD (300 cm vs 400 cm).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Monte Carlo simulation work of Nevelsky et al reported peak floor scatter contributions at 20 cm above the floor to be +3%, −3%, and −5% for iron, PVC, and water, compared to concrete, given a SSD = 400 cm and gantry angle 17° above the horizontal. These magnitudes are larger than those measured with the Cherenkov imaging method (+2.4%, 0.0%, −1.6%), even with a 13° increase in gantry angle (30° vs 17° above the horizontal, more directly impinging the floor) at the shorter SSD (300 cm vs 400 cm).…”
Section: Discussionmentioning
confidence: 99%
“…Nevelsky et al stated “the spectrum of the scattered electrons had a distribution which was almost uniform between a few hundred keV to 4 MeV, then decreased linearly to 6 MeV.” While most of these electrons should be above the threshold for Cherenkov light generation, the energy dependence of the number of photons emitted would deflate the contributions of lower energy‐scattered electrons. For this reason, the Cherenkov imaging method provides a novel qualitative presentation of scatter dose distribution that follow anticipated and simulated trends, however, the accuracy of the quantitative results are limited to within a few percent, depending on the material (and subsequently the energy spectrum of the scattered electrons).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The uncertainty for the MC simulation included room scatter effects 16 from walls, floor, ceiling, and TSI platform in the treatment room since the MC model cannot account for every detailed geometry. Furthermore, the measurements done at the treatment plane can be hard to set up accurately.…”
Section: Discussionmentioning
confidence: 99%